2015
DOI: 10.1016/j.physa.2015.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a new autocorrelation function in low wind speed conditions

Abstract: h i g h l i g h t s• We propose a new mathematical expression to describe the meandering phenomenon.• We employ wind data measured in a nocturnal PBL to obtain experimental ACF. • The new ACF satisfactorily represents the negative lobes of the meandering phenomenon. a b s t r a c tIn this study a new mathematical expression to describe the observed meandering autocorrelation functions in low-wind speed is proposed. The analysis utilizes a large number of best fit curves to show that the proposed theoretical fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
7
0
4
Order By: Relevance
“…Isto pode estar relacionado com a natureza do fenômeno físico responsável pela ocorrência de meandro, todavia, uma investigação mais aprofundada é necessária para embasar tal informação. Moor et al (2015) tiveram um bom ajuste com a autocorrelação dos dados experimentais da componente zonal de velocidade do vento. Porém, para intervalos nos quais o período do meandro é pequeno e o parâmetro de meandro é alto, a função de autocorrelação de Moor et al (2015) apresentou melhor desempenho (Figura 2, painel inferior).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Isto pode estar relacionado com a natureza do fenômeno físico responsável pela ocorrência de meandro, todavia, uma investigação mais aprofundada é necessária para embasar tal informação. Moor et al (2015) tiveram um bom ajuste com a autocorrelação dos dados experimentais da componente zonal de velocidade do vento. Porém, para intervalos nos quais o período do meandro é pequeno e o parâmetro de meandro é alto, a função de autocorrelação de Moor et al (2015) apresentou melhor desempenho (Figura 2, painel inferior).…”
Section: Resultsunclassified
“…Com o objetivo de obter uma expressão que seja capaz de descrever a forma geral e os lobes negativos que caracterizam a autocorrelação de dados experimentais com meandro, Moor et al (2015) propôs uma nova função de autocorrelação (Equação (3)), que utiliza os mesmos parâmetros utilizados na Equação (2).…”
Section: Funções De Autocorrelaçãounclassified
See 1 more Smart Citation
“…Thus, the horizontal wind meandering phenomenon is an important physical component that must be incorporated in air pollution models. These oscillations in the u and v horizontal wind components are practically independent of the atmospheric stability conditions, and are responsible for the presence of negative lobes in observed autocorrelation function (ACF) associated to the horizontal components of the wind vector ( [3], [4]). This meandering ACF oscillatory behaviour makes it very difficult to establish a mean wind direction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Moor et al [6] proposed to utilize a new mathematical formulation to fit the observed low wind speed-meandering autocorrelation functions. This functional form for the horizontal wind velocity components u and v may be written as follows:…”
Section: Introductionmentioning
confidence: 99%